An intragenic duplication in the AFF2 gene associated with Cornelia de Lange syndrome phenotype - Lucia-Campos, Cristina; Parenti, Ilaria; Latorre-Pellicer, Ana; Gil-Salvador, Marta; Bestetti, Ilaria; Finelli, Palma; Larizza, Lidia; Arnedo, María; Ayerza-Casas, Ariadna; Del Rincón, Julia; Trujillano, Laura; Morte, Beatriz; et al. (Frontiers in Genetics, 2024)
We are submitting our manuscript for consideration as an article in Frontiers in Genetics. In this study, we report for the first time an intragenic duplication in the AFF2 gene related with classic Cornelia de Lange syndrome (CdLS) phenotype. We present phenotype data of the affected family members and assess the pathogenicity of the intragenic variant through a combination of clinical phenotype evaluation, clinical exome sequencing, high-resolution array-CGH, deep-sequencing CdLS gene panel, targeted sequencing with Oxford Nanopore Technologies (ONT), gene expression analysis and assessment of X chromosome. In addition, a systematic review of AFF2 variants and their clinical features was performanced. Significant efforts have been devoted to the genetic diagnostic of this case. This is the first time that the AFF2 gene has been linked to CdLS. In this article, the data have been given in chronological order to highlight the main challenge found in the clinical and molecular diagnos